Implikasi Pembatasan Waktu Eksekusi Jaminan Terhadap Kedudukan dan Hak Kreditor Separatis Dalam Undang-Undang Kepailitan - Fauziyyah, Laila (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the time limitation on collateral execution by secured creditors under Law Number 37 of 2004 on Bankruptcy and its implications for legal protection. Secured creditors are entitled to independently execute their security rights, but this right is restricted by a 90-day moratorium and a two-month time limit after insolvency is declared. Using a normative juridical method with statutory and conceptual approaches, the study finds that such restrictions contradict the absolute nature of property rights and potentially downgrade the secured creditor’s status to that of a concurrent creditor. This causes legal uncertainty and financial disadvantage. Therefore, legislative reform and clear procedural guidelines are necessary to ensure the optimal legal protection of secured creditors.